Syntaxin 1B Mediates Berberine’s Roles in Epilepsy-Like Behavior in a Pentylenetetrazole-Induced Seizure Zebrafish Model - Zheng, Yang-Min; Chen, Bo; Jiang, Jian-Dong; Zhang, Jing-Pu (Frontiers in Molecular Neuroscience, 2018)
Epilepsy is a neuronal dysfunction syndrome characterized by transiently and diffusely abnormal discharges of neurons in the brain. Previous studies have shown that mutations in the syntaxin 1b (stx1b) gene caused a familial fever-associated epilepsy syndrome. It is unclear whether the stx1b gene also correlates with other stimulations, such as flashing, and/or mediates the effects of anti-epileptic drugs. In this study, we found that the expression of STX1B was present mainly in the brain and was negatively correlated with seizures in the pentylenetetrazole (PTZ)-induced seizure zebrafish model. The transcription of stx1b was inhibited by PTZ but rescued by valproate, a broad-spectrum epilepsy treatment drug. In the PTZ-seizure zebrafish model, stx1b knockdown aggravated larvae hyperexcitatory swimming and prompted abnormal trajectory movements, particularly under lightning stimulation; meanwhile, the expression level of the neuronal activity marker gene c-fos increased significantly in the brain. In contrast, stx1b overexpression attenuated seizures and decreased c-fos expression levels followingin PTZ-induced seizures in larvae. Thus, we speculated that a deficiency of stx1b gene expression may be related to the onset occurrence of clinical seizuresepilepsy, particularly photosensitive seizures. In addition, we found that berberine (BBR) reduced larvae hyperexcitatory locomotion and abnormal movement trajectory in a concentration-dependent manner, slowed down excessive photosensitive seizure-like swimming, and assisted in the recovery of the expression level of STX1B caused by PTZ. Under downregulation of STX1B, berberine’s roles were limited: it only slightly regulated the two gene expression of stx1b and c-fos and hyperexcitatory motion of zebrafish in dark conditions, but had no effect on the overexcited swimming behavior seen in conjunction with lightning stimulation. These findings further demonstrate that STX1B protein level are negatively correlated with seizure and can decrease sensitivity of the photosensitive response in PTZ-induced seizure zebrafish larvae; furthermore, STX1B may partially mediate the anticonvulsant effect of BBR. Additional investigation regarding the relationship between STX1B, berberine, and seizure could provide new cues for the development of novel anticonvulsant drugs.